SUPERVISION SYSTEM ON THE EXISTENCE OF ILLEGAL TRANSPORT CARS IN BANDA ACEH: A Study of Al- Hisbah Perspective - Shafira Melinda; Faisal (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
The City of Banda Aceh as the capital of Aceh Province which is the center of government, center of religious tourism, education and trade center has caused the level of traffic congestion in the Serambi Mecca area to be high enough to encourage people to use public transportation services as a means of transportation. This study uses a qualitative method with a socio-juridical approach and is descriptive analysis in nature. Primary data collection was obtained in the field while secondary data was obtained from library research. The results of the research show that the enforcement has been carried out by the Department of Transportation in several predetermined locations. Law enforcement at the transportation agency against illegal public transport has carried out direct supervision from the Department of Transportation in collaboration with related parties, actions taken by the transportation agency have also been adjusted to the law or established rules, this authority is given to the police in the form of cooperation conducted with the Department of Transportation. The duties of the Department of Transportation as part of the Al-Hisbah system whose duty is to supervise, coach and submit case files to investigators can also be seen from the actions taken, even though at this time the review conducted found that the L300 Batoh terminal was free from illegal public transportation.